A study on the prevalence of hypertension and factors affecting it among adults aged 25 and above at Nanga Selaut and Nanga Sebirah in Julau district, 19 June to 5 August 2000 : a cross- sectional study - Azizul, Idris; Kuin, Chang Li; Arlina, Nuruddin; Hian, Chai Chiun; Cheng, Lee Chun; Natalia, Che Ishak; Wooi, Yeoh Cheng; Rosidah, Shahbodin; Siti Nawal, Mahmo; Sy. Norashikin, Wan Ahmad (Universiti Malaysia Sarawak, (UNIMAS), 2000)
Hypertension is so far the commonest cardiovascular disorder, posing a major public health challenge to societies in socioeconomic and epidemiological transition. It is one of the major risk factors for cardiovascular mortality, which accounts for 20-50% of all deaths) A cross-sectional study on the prevalence of hypertension amongst residents aged 5 and above and factors affecting it was carried out in Rumah Changgan and Rumah Selan of Nanga Selaut and Rumah Luke Lipa of Nanga Sebirah in Julau. A total of 115 respondents were universally selected for the questionnaire interview and measurements of both blood pressure and body mass index. The overall prevalence of hypertension was found to be 61.7% with 69.6% of men and 56.5% of women were found to be hypertensive. Significant associations between age, educational level, occupation and body mass index with the prevalence of hypertension were found. Nevertheless, there was no statistically significant link between the prevalence of hypertension and positive family history, smoking, excessive dietary salt and alcohol intake. The overall knowledge on hypertension amongst the respondents is poor that 61.7% were proved to have inadequate knowledge. Knowledge of the respondents on risk factors and signs and symptoms of hypertension are generally good (67.0% and 61.7% respectively). Nevertheless, knowledge on complications of hypertension had shown 68.7% of inadequacy among the respondents. The knowledge on signs and symptoms of hypertension is significantly associated with the prevalence of hypertension (p<0.05), however, this is not true for other aspects of hypertension (p>0.05). Although majority of the respondents (113 or 98.3%) has good attitude and practice towards hypertension, it was found not to be statically significant with the prevalence of hypertension as well (p>0.05).